Morpho-metric study of the facial nerve in the Andaman and Nicobar islands population: A Cadaveric study - Sanjay Joseph Fernandes; Chandani Ashok Kumar; Amar Singh L (Asian Journal of Medical Sciences, 2023)
Background: Facial nerve (FN) is the seventh cranial nerve. It is the only cranial nerve which has a long course in a bony canal. From the brain stem, to its terminal branches, it changes its direction 5 times, to innervate, muscles of the second pharyngeal arch. Hence, it is morphometric study and has great clinical importance. Aims and Objectives: This study was conducted to ascertain the variations of the length of facial Never at different parts of the crania so that this study could be helpful for neurosurgeon, radiologist, and clinician, to deal with various diseases of FN. Materials and Methods: Thirty-five (35) male cadaveric temporal bones, were taken out, by removing soft parts attached to it. The FN was exposed. The length of the FN was measured, by digital vernier calliper, in different regions, of the temporal bone. Results: 7.90 (SD±1.24) in petrous part, 3.7 (SD±0.40) in labyrinthine part, 12.13 (SD±0.36) in tympanic, 12.24 (SD±1.86) mastoid part, 15.76 (SD±0.54) length of nerve to stapedius, and 19.06 (SD±0.66) length of branches of chorda-tympani. Conclusion: The present cadaveric study has clinical importance, for the ENT surgeon, neurosurgeon, neurophysician, and the radiologist.